At risk of exclusion in Key Stage 1: an exploratory study of class teachers’ perceptions of the school context and the impact of a Circle of Adults intervention - Cosgrove, Jennifer (2020)
Background Increasing numbers of UK primary school exclusions (Department for Education, 2019a) are a cause for concern due to evidence demonstrating the negative outcomes common for these children (Parsons, Godfrey, Howlett, Hayden, & Martin, 2001). Therefore, an evidence-base to support interventions and practices effective in reducing school exclusion within mainstream primary schools is imperative to inform professional practice. Previous literature has indicated that staff attitudes are influential in mediating exclusionary practices (Hatton, 2013; Pomerantz, 2016). An intervention which seeks to build on such research and support school staff in order to avoid exclusionary practices is the Circles of Adults (CoA) group facilitation approach to problem-solving (Wilson & Newton, 2006). This study aims to investigate the nature of class teachers’ perceptions of a target student at risk of exclusion and explore the classroom context prior to their involvement in a CoA intervention. This research also seeks to explore the class teachers’ experience of the intervention itself and its perceived efficacy. Method Participants within this research were 4 class teachers working with 3 target students in different schools. Following a constructionist epistemology, semi-structured interviews were undertaken with class teachers prior to their involvement in a CoA intervention. Further semi-structured interviews were then held with 2 of these class teachers to follow up on their experiences of the intervention. Thematic Analysis has been used to explore themes within the data. Findings Findings indicated complexities in the way in which teachers construed their student, both prior to and following the CoA. The school context prior to a CoA demonstrated a system of interaction which disempowered the teacher and led to a sense of working in isolation, under immense pressure. The CoA effectively punctuated the system of the school context, enabling teachers to feel supported and part of a cohesive team, promoting more empathic responses within colleague and teacher-student interactions. The perceived value of the CoA intervention was, however, shown to be undermined when concrete actions did not follow.